Disparition du 'dire' dans les verbes de report au discours direct : l'influence de l'ordre énonciatif dans la phrase - Aurélie CECCALDI-HAMET (E-REA)
The position of the utterance reporting direct speech, particularly when final, is more compatible with verbs excluded from the category of “speech verbs” by their lexical meaning (such as the verb shrug). These verbs can thus assume a reporting function within the utterance without presenting a syntactic or semantic link to the citation. These types of utterances present themselves as speech primarily through the use of quotation marks and make it possible under some conditions to temporarily free the reporting verb from the obligation of being semantically linked to the speech (G. Salvan, 2005).